The Influence of Online Shopping Attributes on Customer Satisfaction and Loyalty from the Bukalapak Online Shopping Experience - Sapta Nugraha, Ilham (Jurnal Multidisiplin Indonesia, 2023)
This study aims to determine what factors influence the satisfaction and Loyalty of Bukalapak marketplace customers. The variables used in this study are information quality, Privacy, perceived Security, product variety, product delivery, customer satisfaction and customer loyalty. The population in this study were marketplace users who had used and shopped at the Bukalapak marketplace, with a sample size of 170 respondents. The data collection technique used a questionnaire, and the data analysis technique used was the SmartPLS 4.0 analysis tool. Based on the research results, of the 16 hypotheses studied, 15 hypotheses were accepted: information quality, Privacy, perceived Security, and product variety positively affected customer satisfaction and Loyalty. Perceived Security, information quality, product variety, Delivery and Privacy positively affect customer loyalty through customer satisfaction. The contribution to this research resulted in a model for measuring the effectiveness of the Bukalapak marketplace system that companies can use to develop in the future to increase user satisfaction at Bukalapak.